THE ROLE AND FEATURES OF FINANCIAL PLANNING IN THE ACTIVITIES OF THE ENTERPRISE - SYDORCHUK, Ivanna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The main aspects of financial planning in the enterprise are investigated in the work. The negative and positive factor impact on the financial success and development of enterprises is discussed. The tools that provide improvement of financial indicators of the enterprise and increase of the general level of their development, including sources of formation of financial resources of the enterprise are defined. The sequence of control over the implementation and regulation of the financial plan of the enterprise is proposed. The main tasks of financial planning are as follows: resource balancing of the cycle of production assets on the basis of self-sufficiency and liquidity of debt obligations, resource provision of social measures; rational allocation of capital; prerequisites for financial stability, solvency and creditworthiness determination of the most rational directions of enterprise development that will provide the greatest profit in the planning period; efficient use of financial resources. Factors of influencing the financial planning of enterprises are: technical and economic; organizational and managerial, political and legal and socio-psychological (social). The source of formation of financial resources of the enterprise for the purposes of financial planning is the investment policy, which determines the mechanisms of investment. Investment mechanisms include: own funds mobilization mechanism; the mechanism of mobilization of borrowed funds and the mechanism of mobilization of borrowed funds. The sequence of control over the implementation and regulation of the financial plan of the enterprise includes: formation of the financial plan (operating budgets) of the enterprise; execution of the financial plan; assessment of the risks of influence on the financial stability and development of the enterprise by groups; conducting an analysis of the implementation of the previous financial plan in accordance with the standards for the balance of indicators of the financial activity of the enterprise; choice of technologies and tools to control the implementation of the plan; detection of the result; Regulatory measures to eliminate "Strategic mistakes". Thus, the financial planning of the enterprise is an extremely important component of successful financial management.